PSO-XnB: a proposed model for predicting hospital stay of CAD patients - Miriyala, Geetha Pratyusha; Sinha, Arun Kumar (Frontiers in Artificial Intelligence, 2024)
Coronary artery disease poses a significant challenge in decision-making to predict the length of stay for a hospitalized patient. This paper presents a predictive model, i.e., Particle Swarm Optimized-Enhanced NeuroBoost, which combines the deep autoencoder with an eXtreme gradient boosting model optimized using particle swarm optimization. The model uses a fuzzy set of rules to categorize the length of stay into four distinct classes, followed by data preparation and preprocessing. In this work, the dimensionality of the data is reduced using deep neural autoencoders. The reconstructed data obtained from autoencoders is given as input to an eXtreme gradient boosting model. Finally, the model is tuned with particle swarm optimization to obtain optimal hyperparameters. With the proposed technique, the model achieved superior performance with an overall accuracy of 98.8% compared to traditional ensemble models and past research works. The model also scored highest in other metrics such as precision, recall, and particularly F1 scores for all categories of hospital stay. These scores validate the suitability of our proposed model in medical healthcare applications.